Pengaruh Menghafal Al-Qur’an dengan Program Takhossus terhadap Nilai Pelajaran Tafsir Siswa Kelas XI Madrasah Aliyah Al-Fathimiyah - Mayaly Maghfiroh; Shofwatul Fikriyyah; Vika Madinatul Ilmi; Alya Khoironi Muhibbah; Dini Maulidhah; Faziadatun Ni’mah; Feni Tamimul Ummah; Eny Lathifah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
The purpose of this study was to determine the effect of memorising the Qur'an on the value of tafsir class takhossus lessons at Madrasah Aliyah al-fathimiyah lamongan. is one of the important activities in the life of Muslims. This research method is a quantitative case study type using observation instruments, documents, interviews and questionnaires. The results showed that the effect of memorising the Qur'an with the Takhossus program on the value of the Tafsir lesson of class XI students of Madrasah Aliyah Al-Fathimiyah is that there is no significant effect of memorising the Qur'an on the value of the lesson of MA Al-Fathimiyah takhossus students. Lesson Value Variable (Y) is explained by the variable memorising the Qur'an by 27.40% and the remaining 72.60% is influenced by other variables.